2022
DOI: 10.1111/jcpe.13598
|View full text |Cite
|
Sign up to set email alerts
|

Circulating vitamin C and D concentrations and risk of dental caries and periodontitis: A Mendelian randomization study

Abstract: Aim This Mendelian randomization (MR) study was performed to explore the causal relationship among circulating vitamin C and D levels, dental caries, and periodontitis. Materials and Methods MR analyses were conducted with the inverse variance weighted (IVW) method, weighted median, MR‐Egger approaches, and MR‐robust adjusted profile score method to assess the causal relationships between circulating vitamin C and D concentrations and dental caries, the number of remaining natural permanent teeth in the mouth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
2
14
1
1
Order By: Relevance
“…Our results confirm the recent MR findings that no causal link is present between 25(OH)D and periodontitis (Baumeister et al, 2021). And the recent MR study of the causal relationship between vitamin D and periodontitis supports our conclusions (Z. Hu et al, 2022). However, our analysis provides more solid evidence than the previous study because our study includes various sensitivity methods to preclude the possibility of bias from horizontal pleiotropy and uses a bi‐directional MR method to eliminate reverse causality between periodontitis and 25(OH)D concentration.…”
Section: Discussionsupporting
confidence: 89%
“…Our results confirm the recent MR findings that no causal link is present between 25(OH)D and periodontitis (Baumeister et al, 2021). And the recent MR study of the causal relationship between vitamin D and periodontitis supports our conclusions (Z. Hu et al, 2022). However, our analysis provides more solid evidence than the previous study because our study includes various sensitivity methods to preclude the possibility of bias from horizontal pleiotropy and uses a bi‐directional MR method to eliminate reverse causality between periodontitis and 25(OH)D concentration.…”
Section: Discussionsupporting
confidence: 89%
“…However, we have found very close average values in the incidence of dental caries related to overweight and obesity groups. These results are in full compliance with the studies of Hujoel P. et al [9] and Hu Z. et al [19]. Although, the intake of vitamins (including vitamin D) is often recommended as a protective measure against oral diseases and dental caries, there is currently no persuasive evidence of their protective function in terms of dental caries in adults.…”
Section: Discussionsupporting
confidence: 86%
“…The main factors related to the increased caries incidence in overweight patients are those resulting from nutritional habits as: frequent meals, excessive consumption of fermentable carbohydrates in the food, including carbonated beverages, eating of unhealthy and high-calorie and cariogenic foods [18]. On the other hand, the concentration in the saliva of some micronutrients, such as vitamin D, has a suppressive eff ect on bacterial metabolism and dental plaque maturation [19]. Thus, they could have a protective eff ect on the dental surface demineralization [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mendelian randomization studies showed no causal relationship between dental caries and vitamin D [50]. However, the present study showed no statistical difference in the serum concentrations of 25-OH-VitD between the caries-free and dental caries groups among adolescents.…”
Section: P Valuescontrasting
confidence: 67%